Gallstone ileus: a rare cause of intestinal obstruction - Gama, Barbara N.; C. Rodrigues, Catarina; D.Couto, Bruno; M. Martins, Filipe; Rosa, Isabel; Rosa, Nisalda; Rosa, Madalena (International Surgery Journal, 2024)
Gallstone ileus is a rare complication of choledocholithiasis, characterized by mechanical intestinal obstruction caused by the impaction of a gallstone within the gastrointestinal tract. Patients typically present with nonspecific symptoms, which may be intermittent due to the movement of the calculus along the gastrointestinal tract. We report the case of an 89-year-old patient who presented to our emergency department with intestinal obstruction caused by a gallstone. After hemodynamic stabilization, the patient underwent exploratory laparotomy, followed by enterolithotomy, without addressing the cholecystoduodenal fistula. This condition presents a diagnostic challenge due to its rarity, nonspecific clinical presentation, and the intermittent nature of the disease (tumbling phenomenon). As such, a high index of suspicion is essential, particularly in elderly patients with a history of gallbladder lithiasis. The main controversy in surgical treatment revolves around the extent of surgery and the timing of the procedures. In most cases, isolated enterolithotomy is recommended, as it is a less invasive approach, reducing the morbidity and mortality associated with this condition.